Applications of Environmental Aquatic Chemistry: A Practical Guide, Second Edition - Weiner, Eugene (CRC Press, 2009)
Professionals and students who come from disciplines other than chemistry need a concise, yet reliable guide that explains key concepts in environmental chemistry, from the fundamental science to the necessary calculations for applying them. Updated and reorganized, Applications of Environmental Aquatic Chemistry: A Practical Guide, Second Edition provides the essential background for understanding and solving environmental chemistry problems that arise most frequently.